Application of Matlab/Simulink to Model and Simulate the Extended – Range Electric Vehicles - Huynh, Quốc Việt; Ngo, Thị Ngọc Thắm; Dinh, Tấn Ngọc; Tran, Đình Việt (Journal of Technical Education Science, 2022)
From the outstanding characteristics of electric and hybrid vehicles, the research team studied the electric vehicle model with E-REV, using its features to evaluate the practical applicability of small cars operating in the city. This study aims to design a small 4-seat electric vehicle combined with a gasoline engine to extend the travel distance on a single charge. To simplify the structure and control program, the electric motor and the internal combustion engine are designed to be connected in a series architecture. The E-REV has been simulated to size the range extender by studying the system’s behavior under different drive cycles. A range-extended electric vehicle control algorithm was developed to control the operation of the engine and generator set relative to the state of charge (SOC) of the battery pack. The main objective of the developed algorithm is to maintain the SOC of the battery pack between certain limits predefined by the programmer.